Advanced UFT 12 for test engineers cookbook : over 60 practical recipes to help you accomplish automation tasks using UFT 12 and VBScript /: over 60 practical recipes to help you accomplish automation tasks using UFT 12 and VBScript. (2014) - Bar-Tal, Meir; Wright, Jonathon Lee
No abstract available